THE INFLUENCE OF INCREASING NUMBERS OF INTERNATIONAL STUDENTS ON THE ECONOMY OF POLAND DURING THE LAST DECADE - Jasur Ziyautdinov (Journal Park Publishing, 2024)
Over the past decade, Poland has witnessed a substantial increase in the number of international students, which has had significant economic implications. This article examines the multifaceted impact of this demographic shift on Poland's economy. It explores how international students contribute to the higher education sector, labor market, and overall economic growth. The influx of international students has led to increased revenues for universities, greater demand for goods and services, and enhanced cultural exchange. Additionally, the presence of international students has fostered greater innovation and knowledge transfer, benefiting both academic and professional communities. This study also discusses the challenges associated with this trend, such as integration issues and pressures on local resources. Overall, the economic benefits of increasing numbers of international students in Poland outweigh the challenges, highlighting the importance of supportive policies to sustain this growth.
Keywords: International students, Economic impact, Higher education, Poland, Labor market, Economic growth, Cultural exchange, Innovation, Knowledge transfer, Integration issues.